Public opinion concerning residential sprinkler systems for 1- and 2-family homes - Frattaroli, Shannon (Inj Epidemiol, 2015)
BACKGROUND: Residential sprinkler systems (RSS) are one intervention to prevent fire injury and death, yet there is no literature documenting why RSS homeowners opt to purchase a sprinkler-equipped home. This manuscript describes homeowners’ decisions to purchase homes with residential sprinkler systems (RSS) and their experiences with the technology. It also compares how RSS homeowners and owners of homes without RSS value sprinklers and their levels of support for policies to mandate RSS in new homes. METHODS: We used a national online web panel to sample owners of 1- and 2-family homes, and descriptive methods to analyze the resulting data. RESULTS: Our final sample included 1,357 homeowners of 1- and 2-family homes without RSS and 976 homeowners with RSS. RSS homeowners were more likely than owners of non-RSS homes to indicate they would buy an RSS home in the future (75 % vs. 30 %), and more often indicated a willingness to pay for sprinklers (70 % vs. 40 %). RSS homeowners also expressed higher levels of support for policies to mandate RSS in all new 1- and 2-family homes (48 % vs. 19 %). CONCLUSIONS: The findings offer insight into educational and policy strategies to promote RSS in all new homes, and provide a foundation for future research in this area.